2010
DOI: 10.1002/iroh.201011263
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth of Six Iranian Brachionus Rotifer Strains in Response to Salinity and Food Type

Abstract: Intrinsic rates of population increase (r) were evaluated as a measure of population dynamics of four strains of Brachionus plicatilis and two strains of B. urceolaris from Iran in response to different salinities and feeding algae. Each rotifer strain was cultured at four salinities: 5, 20, 25 and 30‰ and fed with two microalgal species: Chlorella vulgaris and Nannochloropsis oculata. Salinity of 5‰ was critical for all the examined strains, at which r was at minimum and was different from the other salinitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Life table experiments on rotifers are common in environmental risk assessment, ecological and aquaculture research [ 61 ]. At all temperatures, there was no significant difference in T at 0.125 mg/L CPZ treatments compared to the control in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Life table experiments on rotifers are common in environmental risk assessment, ecological and aquaculture research [ 61 ]. At all temperatures, there was no significant difference in T at 0.125 mg/L CPZ treatments compared to the control in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, strains of the same species with different geographic origins can have different biological characteristics and environmental requirements as a result of different genetic backgrounds (Yin & Zhao, 2008;Malekzadeh-Viayeh et al, 2010); thus, it is important to evaluate the potential for growth of the different native strains recently identified. For example, it has been found that salinity affects the lifetime, the reproduction mode and the growth rate of rotifers of the genus Brachionus (Bosque, Hernández, Pérez, Todolí, & Oltra, 2001;Hagiwara, Gallardo, Assavaaree, & Koyani., 2001;Kostopoulou, Miliou, Krontira, & Verriopoulus, 2007;Yin & Zhao, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic growth rate (r) is a variable that integrates survival, fecundity, development time and reproduction (Malekzadeh-Viayeh et al, 2010), while duplication time (Dt) allows to predict the abundance of rotifers at any point of the growth curve and is similar to the generation time (average time between the birth of parents and the birth of their descendants) (Gillooly, 2000). The maximum population density indicates the abundance that can be supported by the culture conditions as a reflection of the changes in survival and reproduction; it also outlines the acclimation history of the population to the experimental conditions (Krebs, 1985).…”
Section: Discussionmentioning
confidence: 99%